In situ determination of the remote sensing reflectance: an inter-comparison - G. Zibordi; K. Ruddick; I. Ansko; G. Moore; S. Kratzer; J. Icely; A. Reinart (Ocean Science, 2012)
Inter-comparison of data products from simultaneous measurements performed with independent systems and methods is a viable approach to assess the consistency of data and additionally to investigate uncertainties. Within such a context the inter-comparison called Assessment of In Situ Radiometric Capabilities for Coastal Water Remote Sensing Applications (ARC) was carried out at the Acqua Alta Oceanographic Tower in the northern Adriatic Sea to explore the accuracy of in situ data products from various in- and above-water optical systems and methods. Measurements were performed under almost ideal conditions, including a stable deployment platform, clear sky, relatively low sun zenith angles and moderately low sea state. Additionally, all optical sensors involved in the experiment were inter-calibrated through absolute radiometric calibration performed with the same standards and methods. Inter-compared data products include spectral water-leaving radiance Lw (λ), above-water downward irradiance Ed(0+,λ) and remote sensing reflectance Rrs(λ). Data products from the various measurement systems/methods were directly compared to those from a single reference system/method. Results for Rrs(λ) indicate spectrally averaged values of relative differences comprised between −1 and +6%, while spectrally averaged values of absolute differences vary from approximately 6% for the above-water systems/methods to 9% for buoy-based systems/methods. The agreement between Rrs(λ) spectral relative differences and estimates of combined uncertainties of the inter-compared systems/methods is noteworthy.